2016
DOI: 10.1039/c5sm01863c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for the fabrication and the characterization of polymer self-assemblies: what are the important parameters?

Abstract: The ability to self-assemble was evaluated for a large variety of amphiphilic block copolymers, including poly(ethyleneoxide-b-ε-caprolactone), poly(ethyleneoxide-b-d,l-lactide), poly(ethyleneoxide-b-styrene), poly(ethyleneoxide-b-butadiene) and poly(ethyleneoxide-b-methylmethacrylate). Different methods of formation are discussed, such as cosolvent addition, film hydration or electroformation. The influence of experimental parameters and macromolecular structures on the size and morphology of the final self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 56 publications
(116 reference statements)
3
74
0
2
Order By: Relevance
“…The glass transition (Tg) of the amphiphile’s hydrophobic block influences chain flexibility and as a result the timescale of aggregate shape transformations, which can range from hours for glassy high Tg polymers to milliseconds for low Tg polymers [1820]. Thus, the rapid mixing followed by an immediate increase in water content within the reservoir during FNP effectively minimizes the chain mobility of the hydrophobic copolymer blocks to stably lock the molecular orientation of the assembly, and this is particularly effective for high Tg polymers like polystyrene [6, 8, 15, 21, 22]. It was determined that the organic solvent must be removed from the assembly quickly to prevent nanoparticle instability and ripening, which can be achieved via flash solvent evaporation or using aqueous reservoirs with large volumes to decrease the solvent concentration [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…The glass transition (Tg) of the amphiphile’s hydrophobic block influences chain flexibility and as a result the timescale of aggregate shape transformations, which can range from hours for glassy high Tg polymers to milliseconds for low Tg polymers [1820]. Thus, the rapid mixing followed by an immediate increase in water content within the reservoir during FNP effectively minimizes the chain mobility of the hydrophobic copolymer blocks to stably lock the molecular orientation of the assembly, and this is particularly effective for high Tg polymers like polystyrene [6, 8, 15, 21, 22]. It was determined that the organic solvent must be removed from the assembly quickly to prevent nanoparticle instability and ripening, which can be achieved via flash solvent evaporation or using aqueous reservoirs with large volumes to decrease the solvent concentration [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophilic weight fraction f PEO reached the values 0.42, 0.56, and 0.68 for the 7/5, 7/10, and 7/15 PLLA-b-PEO copolymers indicating formation of micelle morphology according to Dionzu's work. 34 The formation of such self-assemblies is shown in Fig. 1A.…”
Section: Resultsmentioning
confidence: 99%
“…16,33 The character of selfassemblies of a wide range of PEO-based amphiphilic block copolymers was investigated in a comparative study by Dionzu et al 34 The hydrophilic/hydrophobic fraction was shown to be a significant factor for prediction of the morphology of emerging nano-objects, which are not usually in equilibrium, but kinetically frozen. However, besides molecular parameters, the threshold between micelles and vesicles also depends on details such as (co)solvent system and preparation method.…”
Section: Resultsmentioning
confidence: 99%
“…89 Assim, auto-agregados supramoleculares podem responder a estímulos externos (por exemplo, pH, temperatura, campos magnéticos, luz, processos redox). 90 Na Tabela 4 são apresentadas as modificações mais comuns em PL de maneira a funcionalizá-los.…”
Section: Aplicações E Inovaçõesunclassified